If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) + 7 = 7x Reorder the terms: 5(1 + x) + 7 = 7x (1 * 5 + x * 5) + 7 = 7x (5 + 5x) + 7 = 7x Reorder the terms: 5 + 7 + 5x = 7x Combine like terms: 5 + 7 = 12 12 + 5x = 7x Solving 12 + 5x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + 5x + -7x = 7x + -7x Combine like terms: 5x + -7x = -2x 12 + -2x = 7x + -7x Combine like terms: 7x + -7x = 0 12 + -2x = 0 Add '-12' to each side of the equation. 12 + -12 + -2x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 0 + -12 -2x = 0 + -12 Combine like terms: 0 + -12 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| sr+t=u | | 14=-l/4 | | 19= | | -6(b+7)=-7b-37 | | -3(-4w+1)+15=13 | | 4=2(u-4)-8u | | 12.48+0.11=13.23+0.09 | | 8x-4y=-20 | | 21+2(21+3)+(4*21-5)=c | | 6-8(1+6x)=-2-4x | | 1/2(-2)= | | -5(-17-13d)=-4(10-15d) | | 5(2n-4)-3=-36-3n | | -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t | | 2x+(2/2x-12) | | 2.5x+.5x=6+3.5 | | -(-20-4s)=-2(s+8) | | -8r=4(r-3) | | -50=19+y | | -5n-10=-(8n-1)-8n | | y=(x-2)-1 |